Stabilizing structure and voltage decay of lithium-rich cathode materials. Issue 6 (15th March 2023) - Zubair, Muhammad; Khan, M. Imtiaz; Tufail, Muhammad Khurram; Iqbal, Muhammad Faisal; Fadhali, Mohammed M.; Hassan, Ali; Abd-Rabboh, Hisham S.M.; Alshahrani, Thamraa; Ali, Hazrat; Khan, Misbha Rafiq
Abstract: A major challenge in the discovery of high-energy lithium-ion batteries (LIBs) is to control the voltage stability and Li + kinetics in lithium-rich layered oxide (LrLO) cathode materials. Although these materials can provide a higher specific capacity compared to the current industrially used cathodes, the substantial voltage decay and low Li + diffusion during long term cycling is a serious reason for hindering their practical applications. In order to suppress the voltage decay in lithium-rich cathode materials, herein we introduce the Ti doping into Li1.2 Mn0.56 Ni0.17 Co0.07 O2 cathodes. Also, the influence of Ti doping on the crystalline internal structure, surface chemistry, cycling retention, and Li + kinetics of Li1.2 Mn0.56 Ni0.17 Co0.07 O2 cathodes have been focused in this work. The Ti doping effectively enhances the structural/interfacial stability of the cathode and accelerates the Li + kinetics by expanding the lattice, thereby significantly realizing its voltage/cycling stability and high-rate capability. Experimental results show that Ti-doped LrLO (1% Ti) has achieved high electrochemical kinetics as the discharge cycle retention increased from 61.58% (pristine) to 80.0% after 180 cycles at 1 C, with 150.3 mAh g −1 showing superior high-rate performance at 5C. Ex-situ XRD results confirmed the better structural stability of Ti-doped LrLO after high-rate electrochemical cycling. Our findings provide a suitable element doping strategy for regulating the voltage decay and cycle retention of LrLO, thus promoting their real-world application in future batteries.